DEVELOPING PERFORMANCE ASSESSMENT INSTRUMENT FOR MEASURING SCIENTIFIC ATTITUDES - Debi Shinta; Dadan Rosana (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
This study was aimed at developing an instrument of performance assessment based on the 7E learning cycle model and finding out the result of students’ scientific attitude measurement using the instrument. The study was conducted by adapting the Borg and Gall research method. The subjects of this study were students of grade eight of State Junior High School 2 Binangun, Cilacap, Central Java. Data were obtained from:  first, experts’ judgements in determining the content validity of the instrument. Second, scores of the limited field try-out used in determining the reliability of the instrument, data collection instruments in the form of observation sheet, self assessment, and peer assessment. Third, students’ scientific attitudes in field try-out used to show the result of the measurement using the instrument. Findings show that the developed instrument of performance assessment is valid and reliable; and feasible to be used for measuring scientific attittudes, with measurement results in the good category equally for the three data collection instruments